Implementation of the ATIK model in improving the mastery of new vocabulary in early childhood through flashcards - Lestari, Selvi; Qonita, Hanna Adha; Islamy, Yayang Chisva; Sa'adah, Khaila Nuriyatul; Watini, Sri (Lembaga Penelitian dan Pendidikan Mandala, 2024)
Vocabulary is one of the important aspects of language development in children. Good vocabulary skills will support children's ability to communicate, think, and learn. This study aims to improve mastery of new vocabulary in early childhood using Flashcard media. The reason for this study is because of the low vocabulary in early childhood, which is caused by the lack of utilizing learning media that already exist today. In this study using